Oreocharis pilosopetiolata, a new species of Gesneriaceae from southeastern Guangdong, China - Yang, Li-Hua; Zhou, Ji-Gang; Xu, Ping; Chen, Zhi-Tao; Lu, Yong-Hui; Kang, Ming (Phytotaxa, 2015)
Oreocharis pilosopetiolata, a new species of Gesneriaceae from southeastern Guangdong, China, is described and illustrated. This species resembles O. benthamii var. benthamii, O. benthamii var. reticulata and O. xiangguiensis, but it differs from these species by its leaf and indumentum characters, which are discussed in this paper.